Confined optical modes in small photonic molecules with semiconductor nanocrystals - Donegan, John; Bradley, Louise (My University, 2004)
We report on the coherent coupling of whispering gallery modes (WGMs) in a photonic molecule formed from two melamine-formaldehyde spherical microcavities coated with a thin shell of light-emitting CdTe nanocrystals (NCs). Utilizing different excitation conditions, the splitting of the WGM resonances originating from bonding and antibonding branches of the photonic states is observed, and fine structure consisting of very sharp peaks resulting from lifting of the WGM degeneracy has been detected. Time-resolved measurements showed a slight increase in the spontaneous emission rate of NCs in a photonic molecule when compared to the spontaneous emission rate for NCs coating a single microsphere.
PUBLISHED
Keywords: Physics